Poverty in small-scale fisheries: Old issue, new analysis - Christophe Béné (2018)
Using a new framework combining vulnerability and exclusion as two central dimensions of poverty, this article revisits some of the long-standing beliefs about poverty in small-scale fisheries. We argue that the issue of poverty in fish-dependent communities cannot be reduced to a simple correlation between income poverty and fishery dependence. A more thorough analysis is required that must account for the diversity of fishing-related livelihoods and the complexity of causes of poverty, both inside and outside the sector. The article highlights how poverty in fishing communities often relates to a wide range of socio-institutional factors other than income, including landownership, debt, access to health, education and financial capital, and arginalisation from political decision making. The empirical examples used in this article refer to inland capture fisheries from the Volta and Mekong basins but, arguably, the analysis applies to other fisheries (inland and coastal) in developing countries. © 2011 SAGE Publications.